PENGEMBANGAN MEDIA PEMBELAJARAN GAME TEKA-TEKI GAMBAR PADA MATERI SISTEM GERAK MANUSIA - Kharisma Kharisma; St Syamsudduha; Hamansah Hamansah (Al-AHYA: Jurnal Pendidikan Biologi, 2021)
This research aimed to develop a learning image puzzle media on human motion system materials in MTs Pesantren Laut Perak that was valid, practical, and effective. This four-D research and development study consist of defining, designing, developing, and disseminating stages. The subject of this study was 11 students from class VIII MTs Pesantren Laut Perak Pangkep Regency. The instruments used were the validation sheets, questionnaires, and learning outcomes tests. The results showed the practicality of the media was in a very valid category, with an average value of 3.93. The practicality level of the media was in the practical category, with an average response value of educators and learners of 3.42. The effectiveness of the media was in the category of very effective, with an average completion rate of 85.45%. It appears that the learning media for human motion system material images in MTs Pesantren Perak Pangkep Regency has met valid, practical, and effective criteria.